IMPLEMENTATION OF PROMBING PROMPTING LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN CLASS III SD NEGERI GUNONG KLENG - Yantari, Rika; Khausar; Kistian, Agus (International Journal of Students Education, 2023)
This study aims to determine whether there is an increase in learning outcomes by using the Prombing Prompting learning model in class III SD Negeri Gunong Kleng, Meurebo District, West Aceh Regency. This type of research is classroom action research (CAR). The subjects in this study were all 25 grade III students, consisting of 12 boys and 13 girls. Data collection techniques used are observation and tests. Based on research results from the implementation of the prombing prompting learning model. on the results of pre-action students obtain mastery learning outcomes, namely 6 students or 24% where the average is 55.6. In the first cycle of students who obtained mastery learning outcomes increased to 11 students or 44% with an average value of 65.6. Furthermore, in the second cycle of students obtaining mastery learning outcomes increased to 22 students or 88% with an average of 81.2. Thus it can be concluded that there is an increase in the Application of the Prombing Prompting Learning Model to Improve Student Learning Outcomes in Grade III SD Negeri Gunong Kleng, Meurebo District, West Aceh Regency.